High treatment efficacy by dual targeting of Burkitt’s lymphoma xenografted mice with a 177Lu-based CD22-specific radioimmunoconjugate and rituximab - Weber, Tobias; Mier, Walter; Sauter, Max; Krämer, Susanne; Jäger, Dirk; Haberkorn, Uwe; Krauß, Jürgen (European journal of nuclear medicine and molecular imaging, 2016)
Dual-targeted therapy has been shown to be a promising treatment option in recurrent and/or refractory B-cell non-Hodgkin’s lymphoma (B-NHL). We generated radioimmunoconjugates (RICs) comprising either a novel humanized anti-CD22 monoclonal antibody, huRFB4, or rituximab, and the low-energy β-emitter 177Lu. Both RICs were evaluated as single agents in a human Burkitt’s lymphoma xenograft mouse model. To increase the therapeutic efficacy of the anti-CD22 RIC, combination therapy with unlabelled anti-CD20 rituximab was explored.
Published online: 04 September 2015
Im Titel ist die Zahl "177" hochgestellt
Gesehen am 18.05.2020